2011
DOI: 10.1124/dmd.111.043281
|View full text |Cite
|
Sign up to set email alerts
|

Unique Metabolic Pathway of [14C]Lenvatinib after Oral Administration to Male Cynomolgus Monkey

Abstract: ABSTRACT:Lenvatinib, a potent inhibitor of multiple tyrosine kinases, including vascular endothelial growth factor receptors 2 and 3, generated unique metabolites after oral administration of [ 14 C]lenvatinib (30 mg/kg) to a male cynomolgus monkey. Lenvatinib was found to be transformed to a GSH conjugate, through displacement of an O-aryl moiety, at the quinoline part of the molecule in the liver and kidneys. The GSH conjugate underwent further hydrolysis by ␥-glutamyltranspeptidase and dipeptidases, followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 11 publications
2
20
0
Order By: Relevance
“…Recently, Schlumberger and colleagues in a phase III, double-blind, placebo-controlled trial in patients with radioiodine-refractory differentiated thyroid cancer (SELECT) demonstrated improved progression-free survival and manageable safety profiles with lenvatinib 24 mg once daily (21). However, since lenvatinib is metabolized in the liver (22) through a cytochrome P450 3A (CYP3A)-based mechanism (23), the impaired hepatic function in patients with HCC may affect lenvatinib exposure, and drug doses used in other tumor types may not be appropriate in this patient group (24,25). Therefore, dose-finding studies have been recommended in patients with HCC stratified by Child-Pugh (CP) classes A and B (26).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Schlumberger and colleagues in a phase III, double-blind, placebo-controlled trial in patients with radioiodine-refractory differentiated thyroid cancer (SELECT) demonstrated improved progression-free survival and manageable safety profiles with lenvatinib 24 mg once daily (21). However, since lenvatinib is metabolized in the liver (22) through a cytochrome P450 3A (CYP3A)-based mechanism (23), the impaired hepatic function in patients with HCC may affect lenvatinib exposure, and drug doses used in other tumor types may not be appropriate in this patient group (24,25). Therefore, dose-finding studies have been recommended in patients with HCC stratified by Child-Pugh (CP) classes A and B (26).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro and in vivo studies have demonstrated that lenvatinib is metabolized in both liver and kidney, and it is primarily excreted directly in bile [8, 9]. In a radiolabelled human mass balance study examining total lenvatinib (parent + metabolites), ~64 % of the radioactivity was recovered in the faeces and ~25 % in urine, with only 2.5 % of the administered lenvatinib dose recovered intact [8].…”
Section: Introductionmentioning
confidence: 99%
“…While still quite a few phase-III trials in the first-line setting for HCC are ongoing, testing drugs like Lenvatinib (www.clinicaltrials.gov; NCT01761266), a multikinase TKI inhibiting VEGFR2 and 3 [26], drug treatment for advanced stage HCC beyond sorafenib does not seem to be an easy target for drug development. Currently, a major search for informative biomarkers is taking place that should allow a more targeted approach in subgroups of patients with specific molecular profiles.…”
Section: First-line Treatments For Hcc Beyond Sorafenibmentioning
confidence: 99%